1983
DOI: 10.1111/j.1432-1033.1983.tb07666.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase catalysed aerobic degradation of 5,6,7,8‐tetrahydrobiopterin at physiological pH

Abstract: Theaerobicdegradation of 5,6,7,8-tetrahydrobiopterin at neutral pH is catalysed byperoxidase(EC 1.1 1.1.7) and provides quinonoid 7,8-dihydro(6H)biopterin which readily loses the side chain to yield 7,8-dihydro(3 H)pterin. The latter is in equilibrium with trace amounts of 6-hydroxy-5,6,7,8-tetrahydropterin (covalent hydrate) which is irreversibly oxidised to quinonoid 6-hydroxy-7,8-dihydro(hH)pterin, and this finally rearranges t o 7,g-dihydroxanthopterin.Spectroscopic evidence (ultraviolet, ' H NMR and I3C N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 39 publications
3
42
0
Order By: Relevance
“…3). The BH 2 can be converted back to BH 4 by dihydrofolate reductase (DHFR) in an NADPH dependent manner and the PH 2 can subsequently breakdown to XPH 2 (40). Although the activity of DHFR has not been measured in the ischemic heart, we observed that postischemic BH 2 administration was totally ineffective in increasing CF and did not replete BH 4 .…”
Section: Discussionmentioning
confidence: 66%
“…3). The BH 2 can be converted back to BH 4 by dihydrofolate reductase (DHFR) in an NADPH dependent manner and the PH 2 can subsequently breakdown to XPH 2 (40). Although the activity of DHFR has not been measured in the ischemic heart, we observed that postischemic BH 2 administration was totally ineffective in increasing CF and did not replete BH 4 .…”
Section: Discussionmentioning
confidence: 66%
“…The ultraviolet spectrum of BH2 in 0.1 M phosphate buffer, pH 6.8 has three broad peaks centered at 230 nm (E, 'It has been reported that these patients excrete dihydroxanthopterin which could be derived from PHz [21,[25][26][27][28][29]. (Fig.1A).…”
Section: Identiji:cation Of Ph2 and Bh2mentioning
confidence: 99%
“…242,3934-39431 identified the stable product produced in 0.1 M phosphate pH 6.8, as 7,s-dihydrobiopterin. However, Armarego et al [Armarego, W. L. F., Randles, D. and Taguchi, H. (1983) Eur. J. Biochem.…”
mentioning
confidence: 99%
See 2 more Smart Citations